An Approximate Solution to The Newell-Whitehead Equation by Adomian Decomposition Method - Saad Manaa (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper, we solved the Newell-Whitehead equation approximately using Adomain Decomposition method and we have compared this solution with the exact solution; we found that the solution of this method is so close to the exact solution and this solution is slower to converge to the exact solution when we increase t however,  this method is effective for this kind of problems.